The Renaissance of Astrological Poetry: Scientific Sources of Basinio da Parma’s Astronomicon libri - Chisena, Anna Gabriella (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2022)
The Astronomicon libri of Basinio da Parma is the first Latin astronomical poem written during the Italian humanism movement. According to the information we possess, Basinio composed the poem at the Malatestian court in 1455. It is usually believed that the work is nothing more than an “imitation” of Aratus’s Phaenomena or Hyginus’s De astronomia, and that it lacks real scientific competence in the astronomical and astrological fields. This article, however, aims to present a brief analysis of the poem by examining the results that have emerged through the preparation of its new critical edition. In particular, thanks to both the recognition of a new Basinio autograph and the Greek glosses inserted therein, this article will show how Cleomedes’s Greek astronomical treatise, Μετέωρα (Caelestia), can be considered the main source of Basinio’s Astronomicon libri.